2001
DOI: 10.2165/00019053-200119020-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Multinational Impact of Migraine Symptoms on Healthcare Utilisation and Work Loss

Abstract: The impact of migraine symptoms on healthcare resource utilisation and work loss was similar across most measures in Europe, Latin America, North America and other countries. Total migraine-related work loss due to absenteeism and reduced workday equivalents accounts for most of the economic burden of migraine, regardless of country, in a clinic-based migraine population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 7 publications
1
57
1
Order By: Relevance
“…In addition, as migraine and tension-type headache are comorbid, estimates of migraine alone or tension-type headache alone may inadvertently capture lost productive time due to the other disorder. C o n s i s t e n t w i t h o t h e r s t u dies, 5,6,9,26,27,[30][31][32][33][34] reduced performance while at work was the dominant source (ie, 80% of the lost productive time and 76.6% of the lost productive timerelated cost) of pain-related lost productive time in the US workforce. In previous studies of headache disorders, including daily diary studies of migraine, health-related reduced performance on days at work is a more significant cause of lost work time than absenteeism.…”
Section: -59mentioning
confidence: 99%
“…In addition, as migraine and tension-type headache are comorbid, estimates of migraine alone or tension-type headache alone may inadvertently capture lost productive time due to the other disorder. C o n s i s t e n t w i t h o t h e r s t u dies, 5,6,9,26,27,[30][31][32][33][34] reduced performance while at work was the dominant source (ie, 80% of the lost productive time and 76.6% of the lost productive timerelated cost) of pain-related lost productive time in the US workforce. In previous studies of headache disorders, including daily diary studies of migraine, health-related reduced performance on days at work is a more significant cause of lost work time than absenteeism.…”
Section: -59mentioning
confidence: 99%
“…Migraine headaches are associated with high morbidity and significant loss of productivity [1,2]. Across all age groups, migraineurs are more likely to experience ischaemic stroke than non-migraineurs (relative risk [RR] 2.16, 95% confidence interval [CI] 1.89-2.48), especially migraineurs who have aura (RR 2.88, 95% CI 1.89-4.39) [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Migraine symptoms result in a considerable burden with regard to health care utilization, health care costs, and work/productivity loss due to disability and decreased functional status. [2][3][4][5][6] Clinical trials have demonstrated that sumatriptan (Imitrex®, GlaxoSmithKline) is effective in relieving migraine pain. These studies have established the efficacy of sumatriptan among patients who treated their migraines at a point in which their headache pain was classified as moderate or severe.…”
mentioning
confidence: 99%